Legal Analysis of Notary Competence In Auction Deeds - Lutfianah; Sukarmi, Sukarmi; Rachman, Rino Arief (The Islamic Education and Multiculturalism Foundation, 2025)
Notaries in Indonesia have the authority to make authentic deeds, including auction minutes, as stipulated in Article 15 paragraph (2) letter g of the Notary Position Law (UUJN). However, this provision contradicts the Minister of Finance Regulation (PMK) No. 189/PMK.06/2017 which stipulates that class II auction officials have the authority to make auction minutes. The conflict of norms between these two regulations has created legal uncertainty that risks causing disputes related to the validity of the deed of minutes of auction made by a notary. This research aims to analyze the legal certainty of the deed of minutes of auction made by a notary and propose a legal solution in the form of regulatory harmonization to avoid overlapping authority. The research method used is normative legal research with a statute approach, conceptual approach, and historical approach. The results showed that the inconsistency between UUJN and PMK No. 189/PMK.06/2017 can cause the cancellation of the deed of minutes of auction made by a notary, increase the potential for legal disputes, and cause uncertainty for the parties involved in the auction transaction. Therefore, it is necessary to harmonize the regulations by adjusting the UUJN or PMK so that the rules related to the authority to make the deed of minutes of auction are clearer and do not overlap. This step is expected to provide legal certainty for the community and improve administrative efficiency in auction practices in Indonesia.